Increasing the Quality of Mathematics Learning Through Realistic Mathematics Education Assisted by Manipulative Media - Nur, Muhammad (The Future of Education Journal, 2023)
This research is attracted by the problem of learning mathematics which is still teacher-centered and has not linked the material with the real world and then the emphasis is only patterned on exercises and formulas so that the learning situation causes boredom in students. The student scores of 20 out of 36 students were below the KKM and the proportion of classical completeness was only 44.44%. This study aims to determine the increase in the quality of learning through a realistic mathematics approach assisted by manipulative media can improve teacher skills, increase student activity and improve student learning outcomes at UPT SDN 09 Timpeh. This research method is a type of classroom action research (CAR) in the form of recycling, namely: planning, action or action implementation, observation and reflection. The results showed that: (1) The teacher's skills increased in cycle I, which was 33.5 in the good category. While the score in cycle II increased to 42, with a very good category; (2) Student activity has increased, the first cycle is 18.5 in the sufficient category. While the score in cycle II was 23.95 in the good category; (3) The classical mastery of students' cognitive learning outcomes in the first cycle was 65.35%, while in the second cycle the classical learning mastery increased to 87% with KKM > 75